2015
DOI: 10.1007/s00775-015-1297-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the ruthenium-based drug NAMI-A on the roles played by TGF-β1 in the metastatic process

Abstract: The ruthenium-based drug NAMI-A, characterised by its selectivity against solid tumour metastases, promotes TGF-β1-dependent fibrosis and the reduction of the release of MMPs in the primary tumour. The aim of the study was to examine the interaction of NAMI-A with TGF-β1 in the process of metastasis formation. NAMI-A (1) affects the secretion of TGF-β1 in metastatic MDA-MB-231 cells rather than in non-tumorigenic HBL-100 cells, (2) prevails over TGF-β1 with regard to the invasive capacity of the treated cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
1
12
1
1
Order By: Relevance
“…It is known that sometimes the toxicity in vitro does not correlate with what happens in mice xenograft models. The values found for NAMI‐A and RAPTA‐C were as expected as these compounds are known to have very high IC 50 values in MDA‐MB‐231 and they do not display cytotoxic properties [43,44] …”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…It is known that sometimes the toxicity in vitro does not correlate with what happens in mice xenograft models. The values found for NAMI‐A and RAPTA‐C were as expected as these compounds are known to have very high IC 50 values in MDA‐MB‐231 and they do not display cytotoxic properties [43,44] …”
Section: Resultssupporting
confidence: 76%
“…The values found for NAMI-A and RAPTA-C were as expected as these compounds are known to have very high IC 50 values in MDA-MB-231 and they do not display cytotoxic properties. [43,44] Ruthenium compounds are known for their variation in intracellular interactions, showing localization to nuclear, [45] lysosomal, [46] and mitochondrial [47] compartments, amongst others. To understand the potential target of Ru-IM (1) ruthenium distribution between cytosolic and mitochondrial fractions after 2 and 24 h treatments with 2 μM of compound were analyzed with inductively coupled plasma optical emission spectrometry (ICP-OES) in TNBC MDA-MB-231 and non-malignant breast MCF10a lines (Figure 1).…”
Section: Cellular Viability and Cellular And Organelle Uptake: Results On The Nci 60 Cell Line Panel Five-dose Screenmentioning
confidence: 99%
“…While the mechanism of action of RAPTA-C still remains to be fully elucidated, it has been suggested that the formation of adducts in chromatin histone proteins are involved 18 . This mechanism is different to that observed for the ruthenium(III) compounds mentioned above 19 20 21 . We have also demonstrated the effect of RAPTA-C on the suppression of primary tumor growth in preclinical studies 22 .…”
contrasting
confidence: 85%
“…Furthermore, these complexes have shown some selectivity and the ability to overcome the resistance faced by platinum-based therapeutic agents. NAMI-A is selective for metastatic cancer cells and acts through the TGF-b pathway [50]. KP1019, also known as FFC14A, induces significant upregulation of 284 genes and downregulation of 76 genes, some of which are associated with cell cycle arrest through ROS, mitogen-activated protein (MAP) kinases [51], and chromatin assembly.…”
Section: Ruthenium Compoundsmentioning
confidence: 99%